STRATYFIKACJA A SYSTEM SPOŁECZNY W POLSCE - Domański, Henryk (Wydział Prawa i Administracji UAM, 2009)
The paper analyses the functioning of the social system in Poland from the stratification mechanism perspective. Basing on the results of research carried out in the last decades, the author attempts to identify the conditions in which the recent changes have taken place in the stratification mechanism and the consequences they had on institutions and social attitudes. An analysis of the above leads to a conclusion that those mechanisms function according to a certain logic that is well known both in theory and in practice. Contrary to the theses suggesting a decline of social stratification, there is nothing to suggest that intergenerational transmissions of social status or educational inequalities have weakened. Likewise, marital homogamy and friendship patterns remain substrantial. In the second part of the paper the author attempts to answer the question whether within this stable system of social distances, a “ruling” class and a “middle” class are emerging, as they seem to be (both from the theoretical and empirical point of view) the most predestined classes to play a significant role in the transformation process.
STRATIFICATION AND THE SOCIAL SYSTEM IN POLAND